EDUKASI BAHAYA BULLYING KALANGAN PELAJAR DI SMPN 3 PELALAWAN - Muhammad Basri; Nanda Andriana; Megi Fadli Pratama; Rasita Dewi; Diana Marito; Uly Syahfitri; Nillawati; Rila Kurni; R.Putri Rahmayanti; Felix Boy (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This article discusses education about the dangers of bullying at SMPN 3 Pelalawan. The goal is to increase student awareness of the negative effects of bullying. Activities involve students and use interactive lecture methods. The main focus includes understanding the concepts, signs, and handling of bullying. The results showed an increase in students' understanding of the concept of bullying to 85%, and the ability to recognize signs from 60% to 80%. 75% of students are also able to mention steps to prevent and deal with bullying. This success creates a safer and more inclusive school environment. The article recommends approaches such as open and in-depth discussion to overcome resistance. In the Future suggests focusing on in-person interactions, such as group discussions and simulated bullying. Engaging teachers, parents and measuring long-term impact is important for sustainable behavior change. With a more adaptive approach, it is hoped that this activity will remain effective in overcoming bullying in the future